2008
DOI: 10.1158/1940-6207.prev-08-a53
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A53: Apoptosis initiated in colon cancer cells when treated with muscadine grape extract

Abstract: A53 Research suggests strong correlations between the inflammation process and colon cancer progression, making it an attractive target for anti-inflammatory drugs and compounds. Muscadines (Vitis rotundifolia), a grape species native to the Southeastern United States, are rich in polyphenols containing many biologically important flavonoids that may have potential anti-inflammatory and anti-oxidant properties. Current research has shown that the muscadine grape has a higher total phenolic and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Tang et al . [24] suggested that the molecular mechanism underlying this occurrence was through the reduction of inhibitory kinases, Myt1 and Wee1 [24]. In a similar study conducted by Zi et al .…”
Section: Flavokawain Amentioning
confidence: 95%
See 4 more Smart Citations
“…Tang et al . [24] suggested that the molecular mechanism underlying this occurrence was through the reduction of inhibitory kinases, Myt1 and Wee1 [24]. In a similar study conducted by Zi et al .…”
Section: Flavokawain Amentioning
confidence: 95%
“…For instance, in a research conducted by Tang et al . in 2008 [24], flavokawain A affected the cell cycle regulation of a p53-wild-type bladder cancer cell line (RT4). It was found that flavokawain A increased the amount of p21 and p27 cell cycle regulatory proteins and induced a G1 arrest [24].…”
Section: Flavokawain Amentioning
confidence: 99%
See 3 more Smart Citations